Mengawal Anggota Legislatif Mewujudkan Pemerintahan yang Bersih* - M Muslih (Universitas Batanghari Jambi, 2019)
Legislative members are partners as well as balancing the government in regulating and controlling the government, therefore it is necessary to have a